Bonus Demografi Dan Tantangan Perlindungan Hukum Bagi Tenaga Kerja di Indonesia - nuridin, nuridin (Diktum: Jurnal Ilmu Hukum, 2023)
The demographic benefit is that if the labor market can accommodate a large number of workers, productivity will be maximized. The state of the labor market and the caliber of the workforce in Indonesia need such attention. Due to the accessibility of these employment, some of the issues causing labor absorption are still not ideal. According to the World Bank and IFC, there are a number of key factors that prevent Indonesia from absorbing labor, including a skilled labor shortage, poor infrastructure, muddled policy frameworks, low employment, and an incompatibility between education and business. This UUCK is a part of formulating policies for the labor market in capitalizing on demographic bonus opportunities under the regulation of positive law in Indonesia, including the Labor Law, the Trade Union/Labor Union Law, the Industrial Relations Dispute Settlement Law, and Law Number 6 of 2023 concerning Job Creation. Demographic bonus regulation is important to ensure that demographic bonuses can provide maximum benefits for economic growth and public welfare. This regulation must include labor protection, gender equality, and social protection for workers, as well as be fair and clear in terms of wages, working hours, and other workers' rights. These regulations must be strictly enforced and closely monitored to ensure that workers receive proper protection and are not exploited.